Development and performance of a parsimonious model to estimate temperature in sewer networks. Issue 8 (14th September 2017) - Elías-Maxil, Jorge A.; Hofman, Jan; Wols, Bas; Clemens, Francois; van der Hoek, Jan Peter; Rietveld, Luuk
Abstract: This paper presents a model (inspired by another model) to calculate water temperature in free-surface flow with two main innovations: the convective heat transfer occurs only at the wetted perimeter of pipes, and the model was integrated to commercial software used for hydraulic calculations in drainage systems. Given these innovations, we could reduce the number of modeling input data to calculate the temperature of water and soil in the radial and tangential directions along the pipes, with the advantages of using industry-standard software. To test the performance of the model, it was firstly calibrated in two sets of experiments (to calibrate the hydraulic and the thermal parameters separately), and benchmarked with a third controlled discharge against the case model. The results indicate that in unsteady-state situations the parsimonious model can be twice as accurate as the underlying model because the parsimonious model considers the hydraulic influence of sewer infrastructure.